Diversity and Structure of Diazotrophic Communities in Mangrove Rhizosphere, Revealed by High-Throughput Sequencing - Zhang, Yanying; Yang, Qingsong; Ling, Juan; Van Nostrand, Joy D.; Shi, Zhou; Zhou, Jizhong; Dong, Junde (Frontiers in Microbiology, 2017)
Diazotrophic communities make an essential contribution to the productivity through providing new nitrogen. However, knowledge of the roles that both mangrove tree species and geochemical parameters play in shaping mangove rhizosphere diazotrophic communities is still elusive. Here, a comprehensive examination of the diversity and structure of microbial communities in the rhizospheres of three mangrove species, Rhizophora apiculata, Avicennia marina, and Ceriops tagal, was undertaken using high-throughput sequencing of the 16S rRNA and nifH genes. Our results revealed a great diversity of both the total microbial composition and the diazotrophic composition specifically in the mangrove rhizosphere. Deltaproteobacteria and Gammaproteobacteria were both ubiquitous and dominant, comprising an average of 45.87% and 86.66% of total microbial and diazotrophic communities, respectively. Sulfate-reducing bacteria belonging to the Desulfobacteraceae and Desulfovibrionaceae were the dominant diazotrophs. Community statistical analyses suggested that both mangrove tree species and additional environmental variables played important roles in shaping total microbial and potential diazotroph communities in mangrove rhizospheres. In contrast to the total microbial community investigated by analysis of 16S rRNA gene sequences, most of the dominant diazotrophic groups identified by nifH gene sequences were significantly different among mangrove species. The dominant diazotrophs of the family Desulfobacteraceae were positively correlated with total phosphorus, but negatively correlated with the nitrogen to phosphorus ratio. The Pseudomonadaceae were positively correlated with the concentration of available potassium, suggesting that diazotrophs potentially play an important role in biogeochemical cycles, such as those of nitrogen, phosphorus, sulfur, and potassium, in the mangrove ecosystem.